Exploration of Beliefs about Exclusive Breastfeeding: An Elicitation study with Low-income Women in South Korea - Yeon Bai; Yoonna Lee; Jung E. Lee (International Journal of Nutrition, 2025)
The benefits of exclusive breastfeeding are well-known. Despite the legislative and systemic efforts to promote breastfeeding in South Korea, the nation’s current rate of exclusive breastfeeding (5.2%) during the infant’s first six months is alarming. Under the framework of the theory of planned behavior (TPB), this study elicited the beliefs around exclusive breastfeeding commonly held by low-income women participating in NutriPlus, the community nutrition program. Using a convenient sampling method, online open-ended surveys were conducted with two program clinics in Seoul during spring of 2024. The survey included questions about their demography and beliefs regarding indirect theoretical constructs of the exclusive breastfeeding behavior by listing top three things that came to their mind. A total of 120 NutriPlus clients participated in this survey. Though 53.1% of postpartum women were breastfeeding, only 28.1% were breastfeeding exclusively. Based on most frequently mentioned beliefs, we classified them to behavioral, normative, and control beliefs under TPB. Modal behavioral beliefs were healthy babies (n=87) and mother-baby bonding (n=71) and feeding issues (n=96) and inconvenience resulting from the act of breastfeeding (n=86). Family members seemed to shape both positive (n=122) and negative (n=37) normative beliefs. The presence of support (n=84) mattered to facilitate breastfeeding, while feeding issues (n=98) played as barriers. Promotion efforts need to emphasize breastfeeding knowledge and skill building and include family members and society at large to improve the awareness and transform barriers of breastfeeding to facilitators.
Keywords: Theory of Planned Behavior